TEACHING SPEAKING SKILL OF ENGLISH AS FOREIGN LANGUAGE IN SECONDARY SCHOOL LEVEL - Musdalifah; Raudhatul Islam (Journey: Journal of English Language and Pedagogy, 2022)
The study investigated the teaching speaking skill of English as foreign language in Secondary School level at SMAN 2 Malang from some aspects, the English teacher’s role, the teaching activities, materials, the media, and the assessment of the English teacher. The design of the research belongs to descriptive qualitative research. The participant of this research was an English teacher and the 33 students of X MIPA 2. The setting was SMAN 2 Malang. The data was obtained through observation, interview and documents. The result of this research noted that the teacher has already known role in teaching speaking. Based on the 2013 curriculum students centered was applied and the teacher facilitated the students, teacher created fun speaking activity such as role play, presentation in group and individual, the teacher also used modern media to support the teaching speaking, material that suitable for speaking activities is provided by the teacher based on the syllabus. Fluency, accuracy, pronunciation and expression were the aspect to assess students speaking skill. In this research, the researcher concluded that the teaching speaking skill in SMAN 2 Malang has already well.